Language Use Among Igbo Cultural Associations In Lagos, State, Nigeria - Dr. Dom-Anyanwu Ngozi (MultiTech Publisher, 2023)
This study examines language use among Igbo cultural associations in Lagos state, with a view to identifying their language ideologies, language practices in their meetings and their language management strategies in their meetings. Spolsky's Family language Policy was used as guide. Out of the entire Igbo cultural associations in Lagos State, 25 Igbo cultural associations were purposively sampled. Information was collected through questionnaire and interviews. The result shows that members of Igbo cultural associations in Lagos State had a positive inclination towards Igbo as a language and as a people. In terms of language practice, they used only Igbo in their prayers, breaking of cola nut, and asking for assistance from the association. But, they used only English in writing of minutes, bye-laws, and meeting circular. However, they used code-switching involving Igbo and English during the session of matters arising. It was also found that, although they evinced an implicit language policy, their policy on language in their association was bilingual, involving only Igbo and English, and precluding any other native non-Igbo language. On the whole, although Igbo cultural associations in Lagos State had positive attitude and beliefs toward Igbo, they did not fully reflect it in actual practice during their meetings. It is recommended that Igbo cultural associations, irrespective of setting should endeavor to include the culture of writing all their documents in Igbo, as a deliberate means of safe-guarding the language. Additionally, they should have a monolingual policy in favor of Igbo in their meetings to ensure the vitality of the language in a wholly Igbo cultural setting.